Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan di Nilu Kopi Yogyakarta (Prosiding dan Call Paper Widya Wiwaha, 2023)
This study aims to determine the effect of product quality and service quality on customer satisfaction at Nilu Kopi Yogyakarta. This research is a quantitative research. The sampling technique uses non-probability sampling. The population in this study is all customers at Nilu Kopi Yogyakarta. Respondents were 30 people and used the questionnaire collection method. Data analysis techniques are: 1. Instrument test with Validity and Reliability Test, 2. Classical Assumption Test, 3. Multiple Regression Analysis, 4. Hypothesis Testing with Partial Test (t test) and Simultaneous Test (F test), 5. Coefficient Analysis Determination (R2). Test results and analysis show: 1) Product quality has a significant effect on Nilu Kopi customer satisfaction because the significant value (0.001) is below 0.05 and the tcount value (3.343) greather than ttable value (2.052) with the form of the influence is positive because the regression coefficient value of service quality positive value, namely 0.218. 2) Price has a significant effect on Nilu Kopi customer satisfaction because the significant value (0.000) is below 0.05 and the tcount value (7.080) greather than ttable value (2.052) with the form of the influence being positive because the value of the price regression coefficient is positive, namely 0.420. 3) Product quality (X1) and service quality (X2), have a positive and significant simultaneous effect on customer satisfaction (Y) because the significant value (0.000) is below 0.05 and the Fcount value (168.289) greather than Ftable value (3.35) with the magnitude of the influence of product quality (X1) and service quality (X2) on Nilu Kopi customer satisfaction of 92.6%.
Keywords: Product Quality; Service Quality; Customer Satisfaction